- Aligtifar for the grammarians - collecting and studying - Al - Silme, Muteyaa Allah Bin Awad (Arab Journal for Sciences and Research Publishing, 2018)
The researcher collected what is included under the name "Igtiafar" which is an infraction of some of the sentences of the rules stated by the grammar، with the study of each example and complete the debate around it. The researcher mentioned some of the issues on which the scholars disagreed and then the weighting of what he explained was more likely. He then came to the conclusion of the research in which he supported some statements and disagreed with the others and put his recommendations accordingly.